Outdoor Environmental Education in Higher Education : International Perspectives - Thomas, Glyn V. , 1946-; Dyment, Janet E.; Prince, Heather (International explorations in outdoor and environmental education, 2021)
This book brings together an international group of authors to discuss the outdoor environmental education (OEE) theory and practice that educators can use to support teaching and learning in higher education. The book contents are organised around a recently established list of threshold concepts that can be used to describe the knowledge and skills that university students would develop if they complete a major in outdoor education.